Effect of geometric characteristics of a cluster of micro-contacts on its mechanical and electrical properties. (27th January 2011) - Ervin, John; Sevostianov, Igor
This paper focuses on statistical analysis of the effect of geometrical parameters on the overall resistance of a cluster of microcontacts. We analyse variation in mutual positions and radii of individual contacts from the mean values. It is shown that the effect of perturbations in the mutual positions is very small and the mean distance between the contact centres can be used to estimate the overall resistance. Effect of perturbations in the contact radii is small when the mean radius is small. Using elasticity-conductivity cross-property connections, this result is transferred to the incremental elastic stiffness of the cluster.